Giant right coronary artery aneurysm secondary to Kawasaki disease in child: a case report - Zhang, Shanshan (Int J Clin Exp Pathol, 2015)
Coronary artery aneurysm or ectasia was reported in approximately 15% to 25% of the affected children, particularly in the proximal end of the main blood vessel and the left anterior descending part. Rare patients have been reported with aneurysm in the distal end of the right coronary artery. In this case report, we present a rare case with aneurysm in the distal end of the right coronary artery. Multi-slice computed tomography was performed for the coronary angiography. Aspirin (10 mg/kg body weight per day) and gamma globulin (2 kg/kg body weight) was administrated via intravenous injection. The patient is currently in a healthy status with a 12-month follow up.